2015
DOI: 10.1039/c5nr04723d
|View full text |Cite
|
Sign up to set email alerts
|

Probing charge transfer excitons in a MoSe2–WS2 van der Waals heterostructure

Abstract: We show that the van der Waals heterostructure formed by MoSe2 and WS2 provides a unique system with near degenerate interlayer and intralayer excitonic states. Photoluminescence measurements indicate that the charge transfer exciton states are approximately 50 meV below the MoSe2 exciton states, with a significant spectral overlap. The transient absorption of a femtosecond pulse was used to study the dynamics of the charge transfer excitons at room temperature. We found a lifetime of approximately 80 ps for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
85
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 46 publications
9
85
0
1
Order By: Relevance
“…Previously, some of us have shown that in graphene-WS 2 heterostructures, photocarriers excited in WS 2 can transfer to graphene in 1 ps with high efficiency [28]. In heterostructures formed by different types of TMD monolayers, interlayer charge transfer was also found to be highly efficient, as evident by pronounced photoluminescence quenching effect [29][30][31][32][33][34][35][36], and ultrafast, as revealed by ultrafast laser measurements [37][38][39][40][41]. However, the mechanism of such ultrafast transfer processes is still yet to be understood, given the weak van der Waal nature of the interlayer coupling.…”
Section: Introductionmentioning
confidence: 98%
“…Previously, some of us have shown that in graphene-WS 2 heterostructures, photocarriers excited in WS 2 can transfer to graphene in 1 ps with high efficiency [28]. In heterostructures formed by different types of TMD monolayers, interlayer charge transfer was also found to be highly efficient, as evident by pronounced photoluminescence quenching effect [29][30][31][32][33][34][35][36], and ultrafast, as revealed by ultrafast laser measurements [37][38][39][40][41]. However, the mechanism of such ultrafast transfer processes is still yet to be understood, given the weak van der Waal nature of the interlayer coupling.…”
Section: Introductionmentioning
confidence: 98%
“…Inset: Spatially resolved integrated PL intensity in the spectral range marked in the main panel around pillar A. e,f, Intensity-normalized PL spectra recorded from the HBL at different excitation powers at a position outside the pillar region (e) and on pillar A (f).Besides the power-dependent measurements shown in e,f all spectra were recorded at 10 K subject to strong continuous wave (cw) excitation at 633 nm using a power of 35 µW focused to a spot-size of ∼ 1 µm.4 over sub-picosecond timescales, faster than the exciton lifetime. [40][41][42] The most prominent emission feature from the HBL is at ∼1.38 eV and is attributed to IXs formed by an electron in the MoSe 2 and a hole in the WSe 2 .[7] This attribution is supported by the emission energy and the characteristically asymmetric lineshape featuring red-shifted emission from momentum-indirect IXs [23]. Fig.…”
mentioning
confidence: 99%
“…4 over sub-picosecond timescales, faster than the exciton lifetime. [40][41][42] The most prominent emission feature from the HBL is at ∼1.38 eV and is attributed to IXs formed by an electron in the MoSe 2 and a hole in the WSe 2 .…”
mentioning
confidence: 99%
“…Except for the theoretical calculations, the band offset can be confirmed via microbeam X‐ray photoelectron spectroscopy, scanning tunneling spectroscopy, or submicrometer angle‐resolved photoemission spectroscopy in combination with photoluminescence (PL), such as in the MoS 2 /WSe 2 , MoS 2 /WS 2 , and MoSe 2 /WSe 2 heterojunctions . The shifts of PL and Raman spectra indicate that there is strong interlayer coupling between the two single layers in ultrathin vdW heterostructures regardless of mechanical exfoliated or chemical vapor deposition (CVD) samples, and such coupling can be affected by the atomic registry . The photoexcited electron–hole pairs should not dissociate effectively into free charge carriers within each separate layer of such heterostructures due to the large exciton binding energy, but efficient charge separation at heterojunctions can be realized via photoinduced electron and/or hole transfer.…”
Section: Heterostructures Between Different Tmdsmentioning
confidence: 99%